-3(4-2x)+3=3

Simple and best practice solution for -3(4-2x)+3=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(4-2x)+3=3 equation:


-3(4-2x)+3=3

We simplify the equation to the form, which is simple to understand
-3(4-2x)+3=3

Reorder the terms in parentheses
+(-12+6x)+3=3

Remove unnecessary parentheses
-12+6x+3=+3

We move all terms containing x to the left and all other terms to the right.
+6x=+3+12-3

We simplify left and right side of the equation.
+6x=+12

We divide both sides of the equation by 6 to get x.
x=2

See similar equations:

| 5/2x+2x=3/2 | | X-9/5+3/4=-61/20 | | z^2+2*sqrt(-1)*z-1-2*sqrt(-1)=0 | | -40-7x=6(1-5x) | | z^2-2iz-1-2i=0 | | -49x^4-7x^3= | | 9x-11x=-2(x-4)+4(-9x-11) | | 2b+4=-18-9 | | 6c+4+8= | | 2y-2-2y-7=6y+3-9 | | -7x+32=-6x+8(4-5x) | | (x-3)-25=0 | | -6y=3 | | 3(2x-7)=7x-20 | | 10=z-4 | | .04x+.05y=140 | | 7-3x7/8 | | 0.8x+0.2y=1500 | | -48=-6y-7 | | 3(3n)-3(5)+4n=6+3(n)-2(4n)+5(4) | | 3x+8y=1 | | -8y+-y-5y= | | 5+2x=-5x | | b-8+6b=23 | | 5x-2+1.3(9x-33)=5 | | 11/17=13/u | | 3g+3(2-g)=-4(g+1) | | y=8x-4/5 | | P-1=5+5p-8 | | -5-10u+-7u= | | 3x^3-8x^2-x+10=0 | | 5x-(2x-6)=12 |

Equations solver categories